Implementation of Family Emotional Support on the Level of Compliance With a Low Salt Diet in Elderly Hypertension - Rahmawati Rahmawati; Sonhaji Sonhaji (Sean Institute, 2026)
Background: Hypertension, or high blood pressure, is a common non-communicable disease and a leading cause of illness and death worldwide. One way to manage hypertension is through diet, one of which is adopting a low-salt diet. Consuming too much salt can cause high blood pressure. Emotional support from family is crucial in helping the elderly. This support can take the form of attention, affection, empathy, motivation, and moral encouragement provided by family members. Objective: To describe nursing care with the Implementation of Family Emotional Support with the Level of Low Salt Diet Compliance in Hypertensive Elderly at Health Center, Semarang City. Method: Descriptive case study was used as the following type of research, with elderly subjects Mrs. K 71years old female and Mrs. S 75 years old female. Data were collected by conducting interviews, physical examinations and observations, as well as data collection based on documentation studies. Results: Based on the analyzed study on the provision of interventions with a diagnosis of acute pain related to physiological injury agents of hypertension, knowledge deficit related to lack of exposure to information and sleep pattern disorders related to pain and anxiety, there was a significant decrease in high blood pressure in Mrs. K; Pretest: 174/95 mmHg and Posttest 152/82 mmHg, in Mrs. S; Pretest: 184/92 mmHg and Posttest 160/78 mmHg which was carried out for 15 minutes in one meeting. Conclusion: can overcome high blood pressure levels in Mrs. K and Mrs. S with hypertension.